Relatório de Estágio Profissional "A viagem de uma jovem aventureira: Relatos sobre a descoberta de um niovo mundo - Elisabete Maria Almeida Oliveira (2017)
The internship is seen as the culmination of academic training. It is the stage in which students, future professionals, are confronted with reality, in which the transition from theory to practice is made. It is a period of experience, where all knowledge previously acquired are put into practice and becomes devoted of meaning. This stage, however, deserves to be reflected and described, making all the experiences that we had, in a place initially unknown, but which in the course of time becamed authentic, unique and full of meaningful learning. Thus, this Internship Report appears, a set of pages in which are described a set of reflections and personal experiences, which translate the various moments, marked by different emotions, the difficulties experienced, the activities developed, the decisions made and the tasks taken throug out this year. There is also a study about the students' perception of the values inherent in Physical Education and Sports, which aroused interest throughout the pedagogical practice due to the particularities of the resident group and, finally, a conclusion with a reflection about this topic, its meaning, as well as future perspectives